A104 PATIENT AND PUBLIC INVOLVEMENT (PPIN) IN IBD RESEARCH - A SCOPING REVIEW. (21st February 2022) - Elsolh, K; Neary, E; Seleq, S; Gimpaya, N; Scaffidi, M; Khan, R; Grover, S
Abstract: Background: Over the past 10 years, interest in patient and public involvement (PPIn) in research has grown. Several arguments support the engagement of patients as partners in the research process. Patients with lived experience of a condition can offer their knowledge to study design as experience-based experts, helping researchers incorporate patient-pertinent outcomes. PPIn has also been shown to boost patient enrolment and retention in clinical trials. Benefits, challenges, and best practices of PPIn have been examined in other fields. However, to date, no study has examined PPIn in inflammatory bowel disease (IBD) research. Many factors amenable to research involvement may impact IBD patients' quality of life, including disease morbidity, complications, and efficacy/side effects of therapy. Aims: This review aims to characterize methods of PPIn in IBD research and highlight themes relating to best practices, benefits, and challenges. Methods: We ran a systematic search on MEDLINE, EMBASE, and Cochrane for all IBD research studies in which IBD patients were involved in the research process. PPIn included but was not limited to patient input in one of the following 3 stages: Study Design (prioritization of research topics, outcome selection, study tool development), Study Execution (recruitment, data collection & analysis), and Dissemination of Research. After abstract and full-text screening, 14 studies were selected. Results: Patients were recruited for PPIn through IBD and patient organizations (7/14), outpatient clinics (4/14), tertiary care sites (2/14), and pre-existing patient advisory groups (1/14). The majority of studies (11/14) engaged patients in the development of study materials, which included a physical activity intervention for stoma patients, an IBD pregnancy decision aid, and a quality of life questionnaire. Two studies interviewed patients to determine comprehensibility of survey items and guide revisions. One study involved patients in data analysis and manuscript development. Most consultations were open-ended, including focus groups (8/14) and semi-structured interviews (3/14). According to study authors, PPIn helps guide IBD research priorities by focusing on patient-relevant issues. Authors also cited the role of PPIn in designing patient-friendly study tools. One challenge reported by 2 studies was that PPIn requires patients to have access to high-quality information and requires a significant time commitment, which may contribute to demographic biases. Conclusions: The majority of IBD studies engaged patients in an open-ended format and were engaged in study design, particularly in developing study materials. Authors recommend continuous involvement of patients throughout the research process to address their research priorities. Funding Agencies: None